Aspectos legales de la situación actual de la minería y el impacto del paquete de nuevos decretos legislativos en la actividad minera. Entrevista a Luis Carlos Rodrigo - Cueva Chauca, Sergio (2016)
In this interview, Luis Carlos Rodrigo tells us about the new measures taken by the Government for unlock investments in order to invigorate the economy. Furthermore, he tell us about the participation of new entities in the granting of mining concession, the impact of these new measures in the mining formalization process, the effects of these in the administrative simplification and about relevant aspects uncontemplated by these rules.